Special edition using Microsoft Office Project 2007 (Que Pub., 2007)
Special Edition Using Microsoft ® Office Project 2007 We crafted this book to grow with you, providing the reference material you need as you move toward Project proficiency and use of more advanced features. If you buy only one book on Project 2007, Special Edition Using Microsoft ® Office Project 2007 is the only book you need. THE ONLY DESKTOP PROJECT BOOK YOU NEED - Leverage Microsoft Project 2007 to support your management processes, communication and collaboration within your organization - Manage your project through initiation, tracking, controlling, performance measuring, and closing - Model real life project scenarios with the scheduling engine - Define tasks, milestones, summary tasks, and recurring tasks to create your project schedule - Create task relationships, constraints, and perform advanced actions on tasks - Customize the project to fit your needs - Use views, tables, filters, and groups to review your project and application interface schedule - Manipulate Microsoft Project 2007 data using other Microsoft Office applications - Implement Visual Reports to allow 3D models of project data for sharing and analysis - Master advanced features with built-in and advanced manual techniques " Special Edition Using Microsoft Office Project 2007 continues the great QUE tradition of bringing together all of the features and capabilities of our software in a logical, easy-to-follow manner. With the knowledge and experience that QuantumPM, LLC brings to the domain of project management and to the use of Microsoft® Office Project 2007, this book should be on every desktop!"--Mike Angiulo, General Manager, Microsoft's Office Project Business Unit QuantumPM, LLC is a project, program, and portfolio management product and services firm that helps its clients create pragmatic and valuable solutions to address real world problems. The company combines state-of-the-art tools from Microsoft and other technology leaders, its own expertise, and industry best practices to create solutions that support the way their customers work. QuantumPM services include Management Consulting, Technical Consulting, Training, Hosting Services, Earned Value Management, and Business Intelligence solutions. This book is a culmination of many experiences, people, and industries that together make up QuantumPM, LLC. It includes many insights into Microsoft Office Project 2007 from the experts who have used this tool in the field for many years. Introduction I Getting ...